GLOBAL TRENDS IN PATIENT SAFETY AND SERVICE QUALITY: A BIBLIOMETRIC EXPLORATION FROM CLINICAL PRACTICE TO ORGANIZATIONAL CULTURE - Nadila Rahmi; Arlina Dewi (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Patient safety and quality of service are crucial indicators in evaluating the effectiveness and accountability of healthcare systems. Despite the widespread implementation of clinical interventions and regulatory measures globally, significant challenges remain in ensuring safe and high-quality services, particularly in developing countries. This study aims to explore the trends and directions of research related to patient safety and quality of service during the 2015–2024 period using a bibliometric approach. Data were retrieved from the Scopus database using the keywords “Patient Safety” AND “Quality of Service” and were analyzed using VOSviewer software to visualize keyword networks, temporal trends, and term density. The analysis identified five major clusters in this area of study: (1) clinical interaction and human factors; (2) safety culture and organizational perception; (3) service quality and clinical procedures; (4) healthcare systems and hospital organization; and (5) the role of institutions and workforce. The findings indicate a shift in research focus from technical approaches toward systemic and humanistic perspectives. Communication among healthcare professionals, organizational culture, and technology adoption emerge as key elements in building an effective and sustainable patient safety ecosystem.